2014
DOI: 10.3109/02699052.2014.888477
|View full text |Cite
|
Sign up to set email alerts
|

Brain activation by music in patients in a vegetative or minimally conscious state following diffuse brain injury

Abstract: The presence of STG activation by MS may predict a possible improvement of patients in a VS to MCS and fMRI employing MS may be a useful modality to objectively evaluate consciousness in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 44 publications
1
40
0
1
Order By: Relevance
“…PICO questions 1–3 refer to resting state PET and fMRI, PICO questions 4–6 to passive and active fMRI paradigms. Forty‐four publications were included for final analysis . PICO 1 Should resting state PET be used to diagnose signs of covert consciousness in patients with DoC? …”
Section: Resultsmentioning
confidence: 99%
“…PICO questions 1–3 refer to resting state PET and fMRI, PICO questions 4–6 to passive and active fMRI paradigms. Forty‐four publications were included for final analysis . PICO 1 Should resting state PET be used to diagnose signs of covert consciousness in patients with DoC? …”
Section: Resultsmentioning
confidence: 99%
“…Music listening has a beneficial effect on cognitive processes in people with DOC (Castro et al, 2015) including increased EEG amplitude in alpha and theta bands suggestive of attentional processes (O'Kelly et al, 2013). Case studies suggest music may have diagnostic value to distinguish between vegetative and minimally conscious states, as well as prognostic potential (Okumura et al, 2014). Clinical music protocols for therapeutic intervention have been developed and music-based diagnostic measures have been standardized (Magee and O'Kelly, 2015).…”
Section: Music and Docmentioning
confidence: 99%
“…Music is receiving increasing attention as a stimulus for assessment of awareness given its properties of being a non-languagebased stimulus within the auditory modality that has emotional saliency (Boyle & Greer, 1983;Formisano et al, 2001;Jones et al, 2000;Lichtensztejn et al, 2014;Magee, 2005Magee, , 2007Magee et al, 2014;Okumura et al, 2014;Perrin et al, 2006;Puggina, da Silva, & Santos, 2011;Verger et al, 2014;Verville et al, 2012;Wilson, Cranny, & Andrews, 1992). Neurophysiological studies have revealed that music can promote behavioral responses indicative of arousal and attention in PDOC patients, and most importantly, that significant cortical and autonomic nervous system activity suggest discriminative ability rather than reflex responses .…”
Section: Music Used For Diagnosis In Pdocmentioning
confidence: 99%
“…Neurophysiological studies have revealed that music can promote behavioral responses indicative of arousal and attention in PDOC patients, and most importantly, that significant cortical and autonomic nervous system activity suggest discriminative ability rather than reflex responses . Furthermore, music may not just be a useful tool for evaluation of consciousness, but may stimulate brain activation that can predict patient improvement (Okumura et al, 2014).…”
Section: Music Used For Diagnosis In Pdocmentioning
confidence: 99%